PEMILIHAN JENIS BANGUNAN PELINDUNG PANTAI BONTO BAHARI MENGGUNAKAN METODE ANALITYCAL HIERARCHY PROCESS (AHP) - Chairul Paotonan; Fajar Arif Nurdin (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2020)
Bonto Bahari coastline has two main problems namely erosion and wave attack to the publics housing. On that score, coastal protection is needed to protect the coastline. The approximation in coastal protection are soft and hard approach. Hard approach consist of revetment, seawall, groin, jetty and detached breakwater. The objective of this study is to determine the suitable coastal structure type in Bonto Bahari area. In this study, the method were used in determining of costal structure type is analytical hierarchy process (AHP). Parameters were considered in determined of costal structure type namely ability of structure in protect coastline by wave attract, ability of structure in reducing longshore sediment transport, cohesiveness of local community activity, cohesiveness of existing structure, esthetic, construction method, cost, maintenance, environment impact and availability local material. Based on data analysis, obtained that the structure type has highest score respectively are groin T (0.3189), seawall (0.1881), detached breakwater (0.1839), groin I (0.1627) and revetment (0.1464).